(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Five among the Panchakarmas ’Nasya’ has specific modus operandi in its administration Pharmacotherapeutics and clinical outcomes. Irrespective of Doshik combination pattern, it deals with all diseases of Urdhvajatrugat unlikely of Vaman, Virechan and Basti which are specifically useful in amelioration of kapha Pitta and Vata respectively. The preventive potential of Vaman, Virechan and Basti have sound conceptual base and subsequent clinical observation; however, Nasya for its preventive potential has not been much explored. The present write up is an effort to discuss the opportunities and challenges of Pratimarsha Nasya therapeutics for its preventive and health promotive dimensions.